PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI LINGKARAN KELAS XII - Ninik Ekowatiningsih; Zeni Fatmawati; Ika Purwantini; Siti Aminah (FKIP Unirow Tuban, 2017)
This study aims to improve student learning outcomes through Jigsaw Type Co-operative Model on Class XII Classroom materials at SMK Negeri Widang Pelajar 2017/2018. This type of research is a class action research of cycle model. The subjects of the study were students of Class XII TKR-2 of 31 people. The data were analyzed by descriptive quantitative. The result of the research was the result of increasing mathematics learning through Jigsaw Type Co-operative learning model in Class XII TKR-2 SMK Negeri Widang, the competency standard determine the circle part and its size. The first cycle, the average mathematics learning outcomes in the sufficient category (67.27), but has not reached the learning completeness set. The second cycle, the average mathematics learning outcomes increased to either category (80.45) and has reached the learning completeness criteria.